Fintech : Mapping the Performance of Peer to Peer Lending Credit in Indonesia - Reskiyah, Reskiyah; Darman, Darman; Munawarah, Munawarah; Risendy, Rian (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The era of Globalization 5.0 drives technological innovation across various sectors, including financial services, with the emergence of Financial Technology (FinTech). Peer-to-peer lending (P2P Lending), one of the FinTech products, has become a popular alternative for financing in Indonesia. This study aims to analyze the growth of P2P Lending users, credit performance by region, and the causes of credit defaults. A quantitative descriptive method is employed with a population of 98 P2P Lending platforms registered with the Financial Services Authority (OJK) as of July 2024. Data are analyzed using growth ratio and Non-Performing Loan (NPL) ratio, with findings categorized across six archipelagic regions in Indonesia. The results indicate significant growth in the number of P2P Lending users, particularly in Java. However, this growth raises a high risk of credit defaults, mainly due to the use of loans for consumptive purposes. This study underscores the importance of public financial literacy in managing credit risks to optimize the sustainable benefits of P2P Lending.